Heteropolyacids with Keggin structure supported on silica-alumina - Vazquez, Patricia Graciela (2006)
The behaviour of molybdophosphoric acid, with Keggin structure, supported on different silica-alumina mixtures, obtained by sol-gel method, was studied. Different techniques were used to synthesise the supports. In one of them, commercial alumina was added to a tetraethyl orthosilicate (TEOS) solution, and then this was hydrolysed. In the other preparations, TEOS and aluminium tri-sec-butoxide were hydrolysed, simultaneously or with TEOS prehydrolysis. The catalysts were prepared by incipient wetness impregnation, and different thermal treatments were applied after their leaching with toluene. The specific surface area of the solids was measured, and the nature of the Keggin heteropolyacid species present in the catalysts was characterised by diffuse reflectance spectroscopy and X-ray diffraction. In addition, their acidic properties were evaluated by potentiometric titration with n-butylamine